Monolayer graphene/platinum-modified 3D origami microfluidic paper-based biosensor for smartphone-assisted biomarkers detection - Arda Fridua Putra; Annisa Septyana Ningrum; Suyanto Suyanto; Vania Mitha Pratiwi; Muhammad Yusuf Hakim Widianto; Irkham Irkham; Wulan Tri Wahyuni; Isnaini Rahmawati; Fu-Ming Wang; Chi-Hsien Huang; Ruri Agung Wahyuono (ADMET and DMPK, 2025)
Background and purpose: Imbalances in biomarkers such as dopamine and NADH are linked to neurological and metabolic disorders, including Parkinson’s disease, depression, and stroke, underscoring the need for rapid and accessible diagnostics. This study presents a smartphone-assisted, 3D origami microfluidic paper-based analytical device (µPAD) modified with photochemically synthesized graphene/platinum (G/Pt) nanocatalysts for multiplex colorimetric detection of dopamine and NADH. Experimental approach: G/Pt catalysts were prepared using 2.5 to 10 mM Pt precursors under UV irradiation. µPADs were laser-printed on commercial-grade filter paper, patterned, and folded into three layers of 3D Origami. Key results: The optimized 10 mM G/Pt catalyst significantly improved reaction rates (18× faster), leading to a rapid detection time constant of 6.69 and 4.59 s for dopamine and NADH, respectively. Furthermore, the utilization of 10 mM G/Pt catalyst increased colour intensity (2.48×) on the µPAD platform. An application for smartphones integrated with an image processing algorithm was developed using Kotlin to enable automatic quantification of colorimetric signals from saturation and hue channels for dopamine and NADH, respectively. The detection exhibited the lowest mean absolute percentage errors of 0.52 and 0.07 % as well as a limit of detection of 0.56 and 0.99 mM for dopamine and NADH, respectively. Conclusion: The 3D origami structure facilitates efficient fluid handling and multiplex detection, while the nanocatalyst modification improves pore infiltration and sensitivity. This work demonstrates, for the first time, a cost-effective, portable, and high-performance biosensor for dual biomarker detection, offering substantial promise for point-of-care diagnostics in neurological and metabolic health monitoring.